« Le Diable » de Rita Renoir (1972). Ethnoscénologie d’un mimodrame porno-sataniste - PHILIPPE-MEDEN, Pierre (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
“The Devil” by Rita Renoir (1972): Ethnoscenology of a satanic porn mime drama. Le Diable (The Devil) was staged by Rita Renoir at the Théâtre de Plaisance in Paris in 1972. It is a mime drama devoid of text and music; her body only is present, her breathing, screaming, the forbidden aspects of life and its violence. Alone on the stage, Rita Renoir becomes the witch who evokes the devil and subsequently traps him with her charms. With her back to the public, she bends down exposing her buttocks and her sex, giving the public the role of the devil. The witch engages in copulation with the devil, and this violent lovemaking evokes visions of diabolic, grotesque and libidinous creatures. The male bourgeois audience was offended by the performance and there was even an attempt to rape Rita Renoir on stage, but she received the support of feminist journalists and art critics. This child of Satan and the Women’s Lib pushes the provocation to the extreme and reverses the roles, and it is the public that finds itself exposed to her glaring at them, stripping them and violating them. What is the meaning of Rita Renoir’s staging body and of her porno-Satanist ritual? Our Ethnoscenographic approach of Rita Renoir’s Le Diable consists of a descriptive analysis of a private collection archives of photographs and articles of the printed press.